INVESTIGATION OF OPTICAL AND PHOTOVOLTAIC PARAMETERS OF POLYMER SOLAR CELLS BASED ON DONOR:Y6 ACTIVE LAYER (Scientific journal of the Fergana State University, 2026)
This article presents the results of a study aimed at improving the efficiency of polymer solar cells (PSCs). The optical and photovoltaic properties of the donor polymers PM6 and D18, as well as the non-fullerene acceptor Y6, were investigated. The light absorption spectra, energy level alignments, and interactions between donor and acceptor materials were analyzed. In addition, the absorption spectra of the active layers composed of the Y6 non-fullerene acceptor with PM6 and D18 donors were studied. Experimental results showed that the Y6 non-fullerene acceptor exhibits higher light absorption capability and photovoltaic performance. When combined with the D18 donor in the active layer, a power conversion efficiency (PCE) of 17.2% was achieved.